Opioid and/or Psychotropic Use Increases Intraprocedural Sedation Drug Requirements - Sreeja Sanampudi; Ravi Jayavarapu; Trae Brooks; Driss Raissi (Journal of Clinical Interventional Radiology ISVIR)
Objectives Acute pain management in opioid users can be challenging in the perioperative period. This study focuses on whether use of opioids increases sedation medication requirements in patients undergoing port placement under moderate sedation. Materials and Methods A retrospective review was performed on all patients undergoing port placement between June 1, 2017, and June 30, 2019. Exclusion criteria included receiving general anesthesia, no sedation, and errors in data entry. Data collection included demographics, use of opioids, benzodiazepines, antidepressants, tobacco, alcohol, and sedation data. Results Opioid, benzodiazepine, and selective serotonin reuptake inhibitors (SSRIs)/serotonin-norepinephrine reuptake inhibitors (SNRIs) use was significantly associated with higher sedation drug dose requirements. Patients using opioids required 10.5% higher doses of midazolam compared with nonusers. Benzodiazepine users required 16.3% additional dosage of midazolam than nonusers. Finally, patients on SSRIs/SNRIs medications required 11.8% higher midazolam dosing when compared with nonusers. Conclusion Anticipating higher needs of sedation medications during procedures in patients with history of psychotropic agents use can allow for more effective sedation and patient satisfaction. More patient and provider awareness is needed on this topic, as health care policy is moving toward value-based healthcare, with patient satisfaction surveys being one of its indicators.